Phosphate-Responsive Biomimetic Nanofluidic Diodes Regulated by Polyamine–Phosphate Interactions: Insights into Their Functional Behavior from Theory and Experiment - Perez Mitta, Gonzalo (2017)
There is currently high interest in developing nanofluidic devices whose iontronic output is defined by biological interactions. The fabrication of a phosphate responsive nanofluidic diode by using the biological relevant amine–phosphate interactions is shown. The fabrication procedure includes the modification of a track-etched asymmetric (conical) nanochannel with polyallylamine (PAH) by electrostatic self-assembly. PAH is the arcaetypical model of polyamine and it is further used to address the nanochannels with phosphate responsivity. In order to explore the influence that phosphate in solution has in the conductance of the modified nanochannels, current–voltage measurements using different concentrations of phosphates are performed. Furthermore, to have a complete physicochemical understanding of the system, experimental data is analyzed using a continuous model based on Poison–Nernst–Planck equations and compared with results obtained from stochastic Monte Carlo simulations.